(untitled) (Journal of actual problems of jurisprudence, 2022)
The article proposes to define standards of conduct not only for the official, but also for other members of society in order to find new ways to eliminate corruption. The main idea of ​​the study is to fight corruption not at the level of a civil servant, but at a time when the concept of corruption is still in its infancy, at the stage of formation of young people’s consciousness. That is, it is recommended to focus all efforts on educational institutions of the country. According to the author, this is where the formation of human consciousness can still be influenced. It is also noted that special attention should be paid to the formation of an anti-corruption culture. In search of an answer to this question, the author studied the legislation of the Republic of Kazakhstan on anti-corruption, political decisions, as well as foreign best practices. According to the article, the Anti-Corruption Law of the Republic of Kazakhstan of 2015 contains 14 anti-corruption measures, but their 13th is aimed at controlling, prohibiting and restricting certain actions of civil servants, and only one measure aimed at creating anti-corruption behavior among young people. According to the author, the relationship between teachers and students is beyond the scope of law. Evidence of this is the lack of a restrictive norm that restricts teacher activities and imposes liability on informal interactions with students, as well as a lack of law enforcement practice to hold teachers accountable.In this regard, the Russian experience in the fight against corruption is presented. In particular, criminal liability for corruption for the teaching staff of the university arises along with other government officials. Russian legislature and law enforcement practice recognize university professors as subjects of corruption. That is, university teachers are criminally liable for bribery if they receive a gift or money from students for taking an exam. Department of Criminal Law, Criminal Procedure and Criminalistics of Al-Farabi Kazakh National University in the framework of the discipline "Legal framework of anti-corruption" The competition for the best video on anti-corruption was held among the students of the course. It was decided to hold such an annual competition in the tradition of the university. Keywords: anti-corruption; formation of an anti-corruption culture; relationship between teachers and students.